Educational Cases Developing in Non-school Activity of Primary School Children - Ukropova A.V (Moscow State University of Psychology and Education, 2015)
The article presents testing results of educational cases. The cases were developed for first grade students based on «The world around us» topical area. The sample included 84 first-grade pupils of the two Moscow schools. The experimental group participated in development activities. The article presents fragments of two developing classes based on a textbook «The world around us» by A.A. Pleshkov. Classes were based on discussion of the methasubject content of the such various phenomena as characteristics of living and nonliving, the existence of things in different historical time (now and 200 years ago). In this paper the ability to analyze, compare, to establish causal relationships, to reflect the mode of action were considered as methasubject competencies. Development of these competencies in school-children was evaluated by the diagnosis method based on A.Z. Zak theoretical thinking. According to the diagnosis results, after the developmental activities, metasubject competencies development indicators in the experimental group significantly improved in comparison with indicators prior to specialized training. Figures have not changed in the control group, so the data lead to the conclusion that the educational cases content has a positive effect on the development of metasubject competencies in first year school children.